2014
DOI: 10.1371/journal.pone.0106281
|View full text |Cite
|
Sign up to set email alerts
|

Use of SLAM and PVRL4 and Identification of Pro-HB-EGF as Cell Entry Receptors for Wild Type Phocine Distemper Virus

Abstract: Signalling lymphocyte activation molecule (SLAM) has been identified as an immune cell receptor for the morbilliviruses, measles (MV), canine distemper (CDV), rinderpest and peste des petits ruminants (PPRV) viruses, while CD46 is a receptor for vaccine strains of MV. More recently poliovirus like receptor 4 (PVRL4), also known as nectin 4, has been identified as a receptor for MV, CDV and PPRV on the basolateral surface of polarised epithelial cells. PVRL4 is also up-regulated by MV in human brain endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…Paramyxoviral RBPs categorize according to functionality into three groups: hemagglutinin-neuraminidase (HN), hemagglutinin (H), and attachment (G) glycoproteins. HN RBPs bind and hydrolyze sialic acid (Villar and Barroso 2006), H RBPs are presented by morbilliviruses and recognize SLAMF1 and nectin-4 receptors (Bieringer et al 2013;Birch et al 2013;Noyce, Delpeut, and Richardson 2013;Sakai et al 2013;Melia et al 2014;Ader-Ebert et al 2015;Alves et al 2015;Feng et al 2016;Khosravi et al 2016), and most henipaviral G RBPs are specific to ephrin receptors (Bonaparte et al 2005;Negrete et al 2005;Bowden, Jones, and Stuart 2011;Pernet, Wang, and Lee 2012;Rissanen et al 2017). SBPA of known paramyxoviral HN, H, and G RBP structures has shown that these viral proteins segregate according to receptor-specificity (Bowden et al 2008;Lee et al 2015;Rissanen et al 2017;Stelfox and Bowden 2019;Pryce et al 2020) (Fig.…”
Section: Paramyxovirus Rbps: Pathways To Unique Viral Tropism Charactmentioning
confidence: 99%
“…Paramyxoviral RBPs categorize according to functionality into three groups: hemagglutinin-neuraminidase (HN), hemagglutinin (H), and attachment (G) glycoproteins. HN RBPs bind and hydrolyze sialic acid (Villar and Barroso 2006), H RBPs are presented by morbilliviruses and recognize SLAMF1 and nectin-4 receptors (Bieringer et al 2013;Birch et al 2013;Noyce, Delpeut, and Richardson 2013;Sakai et al 2013;Melia et al 2014;Ader-Ebert et al 2015;Alves et al 2015;Feng et al 2016;Khosravi et al 2016), and most henipaviral G RBPs are specific to ephrin receptors (Bonaparte et al 2005;Negrete et al 2005;Bowden, Jones, and Stuart 2011;Pernet, Wang, and Lee 2012;Rissanen et al 2017). SBPA of known paramyxoviral HN, H, and G RBP structures has shown that these viral proteins segregate according to receptor-specificity (Bowden et al 2008;Lee et al 2015;Rissanen et al 2017;Stelfox and Bowden 2019;Pryce et al 2020) (Fig.…”
Section: Paramyxovirus Rbps: Pathways To Unique Viral Tropism Charactmentioning
confidence: 99%
“…The specific interaction of the viral H and F glycoproteins with the host cell receptor(s) determines host susceptibility, tissue tropism and viral pathogenesis. However, because morbilliviruses infect a number of different cell types in vivo including leucocytes, epithelial, endothelial and neural cells, more than one receptor type is required [ 59 ].…”
Section: Clinical Signs Pathogenesis and Pathologymentioning
confidence: 99%
“…Morbillivirus infections caused by MeV, CDV, and DMV share similar patho‐morphological features . The same type of morbillivirus entry receptors was identified in multiple host species . These facts, along with the common phylogenetic origin of morbilliviruses, support the idea of common basic pathogenetic mechanisms in all morbillivirus infections.…”
Section: Introductionmentioning
confidence: 52%
“…However, the role of SLAMF1 and other viral receptor molecules in infection outcome in Cetaceans and possible interspecies transmission remains unknown . The poliovirus receptor‐like 4 (NECTIN4) molecule has been identified as the epithelial cell receptor for MeV, PDV, CDV and peste‐des‐petits‐ruminants virus (PPRV) . Basigin ( BSG, CD147 ), which could be of special interest in SSPE‐affected patients, acts as a (cyclophilin B‐coated) MeV cell entry receptor on cells not expressing the SLAMF1 molecule, such as epithelial or neuronal cells.…”
Section: Introductionmentioning
confidence: 99%